THEORETICAL AND PRACTICAL SIGNIFICANCE OF DEVELOPING LEGAL CULTURE IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2026)
The article provides feedback on the theoretical and practical importance of developing legal culture.